(untitled) (Journal of Environmental Science Studies, 2023)
In low-head hydraulic structures, the prevention against local scouring of the river bed downstream of concrete aprons must be required during flood stages. Generally, protection blocks are installed downstream of the apron, but they do not control the flow passing through the blocks to reduce the velocity near the bottom. In most of river fields, the installation of protection blocks may not help protect the river bed. In the case of low drop-structures, hydraulic jump occurs during flood stages just below the drop-structures. The main flow near the bottom continues far downstream, and a local scouring is formed. In the case of the movable weir, a local scouring occurs downstream of the weir during flood stages. There is little information on the countermeasure against the local scouring below the movable weir during flood stages. Recently, the authors proposed the installation of consecutively assembled boulders instead of protection blocks. This paper presents the effect of installing consecutively assembled boulders on the prevention of local scouring for both low drop-structures and movable weirs. The effect of seepage on reducing flow velocity near the bottom has been shown, the comparison between the installation of protection blocks and the installation of consecutively assembled boulders has been discussed. In the case of the movable weir, the flow velocity near the bottom below the protection blocks is always larger than that below the assembled boulders, in which the effect of the deflected flow formation by the support pier is not negligible.